The effect of e-marketing on achieving competitive advantage - Sharif, Bakhtiar Aubaid; Salih, Hawta Ahmad (Sulaimani Journal for Humanities, 2023)
The current study seeks to clarify and determine the extent of the impact of e-marketing on gaining a competitive edge in the sulaimani malls. It also analyzes the relationship between them in those malls. We started from a problem that was expressed by a number of intellectual and practical questions. The researchers used the analytical descriptive method in his current study. To accomplish the study's goals and provide answers to the earlier queries, researchers adopted a hypothetical model that reflects through how the studied variables interact and how they are affected. This was subjected to a set of statistical tests through (SPSS v24). The study population represents almost exclusively malls of sulaimani. The questionnaire served as the main method for gathering data and information for the study. 325 questionnaires were distributed to the employees, and 285 questionnaires were returned for analysis. Based on the findings, the study found that e-marketing has a direct impact on gaining a competitive advantage and that the e-marketing and competitive advantage are related in a reciprocal manner.
Keywords: Keywords EMarketing; Competitive Advantage; Marketing Intelligence